Urgensi Peran Pemimpin dalam Manajemen Perubahan di Lingkungan Organisasi Pendidikan Islam: Sebuah Analisis Konseptual - Suandi, Ari (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This study aims to analyze the urgency of the leader's role in change management within the Islamic educational organizational environment, focusing on understanding the dynamics of organizational change, factors influencing resistance to change, and effective strategies for reducing such resistance.Method – Employing a conceptual analysis approach, this research outlines key concepts such as "change management," "the leader's role in Islamic education," and "resistance to change." Data was collected through an extensive literature review, encompassing journal articles, books, and other relevant academic sources to comprehensively understand the research subject.Findings – The findings assert that change management requires a systematic process, involving the application of appropriate knowledge and resources to influence impacted individuals. The leader's role is a key catalyst in motivating and directing organizational members to accept and adapt to change. Additionally, a deep understanding of resistance to change and the development of effective strategies to mitigate it are identified as crucial factors in achieving successful change management in the context of Islamic education. Research Implications – This study has significant implications for improving the quality of education and the sustainability of Islamic educational organizations facing future challenges. However, it is limited by its focus on a conceptual approach without empirical testing, thus further research is needed to test the application of change management theory in actual practice within the Islamic educational environment.